Depressive symptoms predict non‐completion of a structured exercise intervention for people with Type 2 diabetes. Issue 4 (25th August 2015) - Swardfager, W.; Yang, P.; Herrmann, N.; Lanctôt, K. L.; Shah, B. R.; Kiss, A.; Oh, P. I.
Abstract: Aim: To quantify the impact of depressive symptoms on completion of exercise‐based rehabilitation for Type 2 diabetes management. Methods: Depressive symptoms were assessed using the Center for Epidemiological Studies Depression scale in a prospective cohort of consecutive patients with Type 2 diabetes entering a 6‐month hybrid (home‐ and clinic‐based) exercise rehabilitation programme. Attendance at exercise sessions was monitored and programme completion/non‐completion was ascertained. Results: Of the programme participants ( n =624, mean age 55.6±10.5 years, 47% male), 26.8% endorsed significant depressive symptoms (depression score ≥16) and 68.1% completed the intervention, attending 54.6±30.0% of supervised exercise sessions. Baseline depressive symptoms (depression scale score ≥16) increased the risk of non‐completion [hazard ratio 1.49 (95% CI 1.10–2.03); P = 0.010], and predicted fewer sessions attended (β=‐2.1, P = 0.002) in adjusted models. A depression score threshold of ≥10 (48.4% of participants) predicted non‐completion [hazard ratio 1.60 (95% CI 1.19–2.17); P = 0.002) with optimum accuracy. Non‐completions resulting from lack of interest (18.9 vs. 11.0%; P = 0.026) and medical complications (14.6 vs. 6.6%; P = 0.006) were more common among participants with depression scores ≥10. Greater hazard ratios for depression scores ≥10 were observed in subgroups not currently using insulin [hazard ratio 1.70 (95% CI 1.24–2.33); P = 0.001), or an antidepressant [hazard ratio 1.83 (95% CI 1.32–2.54); P <0.001]. Conclusions: Depressive symptoms were highly prevalent among participants with Type 2 diabetes entering exercise‐based rehabilitation, and even mild depressive symptoms posed a significant barrier to completion. Depression screening may help target additional supports to facilitate completion of exercise interventions for people with Type 2 diabetes. What's new?: In a cohort of people with Type 2 diabetes entering a structured exercise intervention, depressive symptoms were highly prevalent and frequently untreated. During the exercise intervention, even mild depressive symptoms posed a significant barrier to completion, particularly in participants who were untreated for depression or did not yet require insulin therapy. Depressive symptoms in people with Type 2 diabetes affect health behaviours; however, screening for the associated risks in exercise programmes will require alternative thresholds and consideration of additional clinical characteristics.